Production of ’Prata Anã’ banana as affected by the application of phosphate fertilizer, in four cycles - Silva, José Tadeu Alves da; Rodrigues, Maria Geralda Vilela (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the response of irrigated 'Prata Anã' banana (AAB) to soil application of phosphorus, in four production cycles. The experiment was carried out in the semiarid region of the north of the state of Minas Gerais, Brazil, in a clayey Oxisol, with very low available P (4.6 mg dm-3, Mehlich). A randomized complete block design was used, in a 5x4 factorial arrangement, with five doses of triple superphosphate (0, 50, 100, 200, and 300 g P2O5 per plant per year), four production cycles, and four replicates. In the first cycle, the soil application of P increased plant height, pseudostem diameter, weight and number of fruits per bunch of banana; however, banana plants did not respond to P application in the second, third, and fourth cycles. 'Prata Anã' banana, even when grown in soil with low P content, responds to the application of this nutrient only in the first production cycle.